Role of oral teriflunomide in the management of multiple sclerosis - Tanasescu, Radu; Evangelou, Nikos; Constantinescu, Cris S. (Dove Press, 2013)
The landscape of the treatment of relapsing–remitting multiple sclerosis is changing fast. Several oral treatments have shown benefit and generate much interest because of the convenience of their administration. Two oral compounds, fingolimod and teriflunomide, have been approved in relapsing–remitting multiple sclerosis, while others have completed Phase III trials and are awaiting review for registration. Teriflunomide is a pyrimidine synthesis inhibitor with selective immunomodulatory and immunosuppressive properties that have shown consistent efficacy in clinical trials, and a good safety profile. This paper provides an overview of the mechanisms of action and efficacy and safety results from clinical trials with this drug. The role of teriflunomide in the treatment of relapsing–remitting multiple sclerosis is discussed.